A sandwich-type electrochemical aptasensor for Mycobacterium tuberculosis MPT64 antigen detection using C60NPs decorated N-CNTs/GO nanocomposite coupled with conductive PEI-functionalized metal-organic framework. (September 2019) - Chen, Yuhan; Liu, Xinzhu; Guo, Shuliang; Cao, Jun; Zhou, Jing; Zuo, Jianli; Bai, Lijuan
Abstract: The present work described a novel sandwich-type electrochemical aptasensor for rapid and sensitive determination of Mycobacterium tuberculosis MPT64 antigen. Herein, a novel carbon nanocomposite composed of fullerene nanoparticles, nitrogen-doped carbon nanotubes and graphene oxide (C60 NPs-N-CNTs/GO) was facilely synthesized for the first time, which not only possessed a large specific surface area and excellent conductivity, but also exhibited outstanding inherent electroactive property, and therefore served as nanocarrier and redox nanoprobe simultaneously. Gold nanoparticles (AuNPs) was then uniformly anchored onto the surface of such nanocomposite via Au–N bonds to bind with MPT64 antigen aptamer Ⅱ (MAA Ⅱ), forming the tracer label to realize generation and amplification of electrochemical signal. Additionally, conductive polyethyleneimine (PEI)-functionalized Fe-based metal-organic framework (P-MOF) was used as a sensing platform to absorb bimetallic core-shell Au–Pt nanoparticles (Au@Pt), which could accelerate electron transfer and increase the immobilization of MPT64 antigen aptamer Ⅰ (MAA Ⅰ). After the typical sandwich-type protein-aptamer recognition, the inherent electroactivity of the tracer label was provoked by tetraoctylammonium bromide (TOAB), leading to a well-defined current response. Under the optimum condition, the proposed aptasensor showed a wide linear range for MPT64 detection from 1 fg/mL to 1 ng/mL with a limit of detection (LOD) as low as 0.33 fg/mL. More importantly, it was successfully used for MPT64 antigen detection in human serum, exhibiting a promising prospect for TB diagnosis in clinical practice.